Neuronal correlates of cognitive reappraisal in borderline patients with affective instability - Schulze, Lars; Domes, Gregor; Krüger, Alexander; Berger, Christoph; Fleischer, Monika; Prehn, Kristin; Schmahl, Christian; Grossmann, Annette; Hauenstein, Karlheinz; Herpertz, Sabine (Biological psychiatry, 2011)
Background - Borderline personality disorder has been characterized by enhanced emotional reactivity and deficient emotion regulation in behavioral and functional imaging studies. We aimed to validate patients' difficulties in the cognitive regulation of negative emotions and investigated if emotion regulation deficits are restricted to the decrease of negative emotions. A cognitive reappraisal paradigm was used and hence a regulation strategy that is typically applied in cognitive-behavioral therapy. - Methods - Fifteen unmedicated female borderline patients with affective instability and 15 healthy female control subjects underwent functional magnetic resonance imaging during a delayed reappraisal paradigm. Hemodynamic responses were measured in response to aversive pictures in an initial viewing phase and a subsequent reappraisal phase with three different conditions: decreasing, increasing, and maintaining the initial emotional reaction. - Results - Patients demonstrated enhanced activation of left amygdala and right insula during the initial viewing of aversive stimuli. During attempting to decrease the initial emotional reaction, patients showed attenuated activation of the left orbitofrontal cortex and increased activation of the bilateral insula. The attempt to increase negative emotions resulted in enhanced activity in amygdala and insula, whereas no group differences were found. - Conclusions - The results point to the role of two distinguishable processes of emotional difficulties in borderline personality disorder: enhanced emotional reactivity as well as deficits of voluntarily decreasing aversive emotions by means of cognitive reappraisal. The results suggest the neuronal substrate of deficits in explicit emotion regulation in the orbitofrontal cortex, which is in line with previous findings of a dysfunctional prefrontal network in borderline personality disorder.